2015
DOI: 10.1039/c5cc00198f
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of ionic liquid anion–solute–antisolvent interactions for the purification of acetaminophen

Abstract: Hydrogen bond donating cosolvents have been shown to significantly reduce the solubility of acetaminophen (AAP) in ionic liquids containing the acetate anion. Reduced solubility arises from competition for solvation by the acetate anion and can be used for the design of advanced separation techniques, illustrated by the crystallization of AAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 35 publications
0
59
0
Order By: Relevance
“…Meanwhile, the results also follow the trend of the solubility of ibuprofen in such ILs, suggesting that the stronger electrostatic energies between anions and ibuprofen, the higher solubility of ibuprofen. This finding clearly demonstrates that the ILs, containing [AcO] − anion, are considered to be the most promising solvents for drug dissolution, and they can also be used in drugs crystallization …”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Meanwhile, the results also follow the trend of the solubility of ibuprofen in such ILs, suggesting that the stronger electrostatic energies between anions and ibuprofen, the higher solubility of ibuprofen. This finding clearly demonstrates that the ILs, containing [AcO] − anion, are considered to be the most promising solvents for drug dissolution, and they can also be used in drugs crystallization …”
Section: Resultsmentioning
confidence: 74%
“…They found that the strong solvation of acetaminophen in ILs was dominated by the strong HB interaction between acetaminophen and anions, while the cations played a minor role. In another study, they found that the favorable solvation of lidocaine in imidazolium‐based ILs did not only result from the HB interactions between lidocaine and anions but also from the electrostatic interactions between lidocaine and cations, which was different from conventional experimental results that the cations played a negligible role . Furthermore, Myerson et al used COSMO‐RS calculations to demonstrate that both anions and cations form the HB interactions with the drugs, which were considered as one of the main contributing factors for the favorable solubility.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The use of ILs for the purification of APIs has not been widely investigated, with only ah andfulo fl iterature reports. [14][15][16][17][18][19] Smith et al investigated the solubility of ibuprofen and acetaminophen in two very similar ILs, with the only difference asubtle variation of the alkyl chain length of the imidazolium cation used. Both ILs featured the same hydrophobic and weakly interacting anion [PF 6 ] À .T he scope of the study was to investigate the potentialt ou se ILs in future crystallization processes of the two pharmaceuticals, by investigating the solubility, [14] whereas the group in al ater paper demonstrated the crystallization of acetaminophen from the IL.…”
Section: Introductionmentioning
confidence: 99%
“…[7] One of the most important factorsd etermining the properties of an ionicl iquid (IL) is the basicity of its anion. [8][9][10][11][12][13] Their basicities can to some extent be inferred from the equilibrium constant of their corresponding acids' dissociation at low concentrations in water [2,14] (pK a values) but the accuracyo fs uch deduction is limited by solvent (medium)a nd concentratione ffects. [8][9][10][11][12][13] Their basicities can to some extent be inferred from the equilibrium constant of their corresponding acids' dissociation at low concentrations in water [2,14] (pK a values) but the accuracyo fs uch deduction is limited by solvent (medium)a nd concentratione ffects.…”
Section: Introductionmentioning
confidence: 99%